Effects of menstrual cycle phase on workload, recovery and stress in elite female field hockey players: a pilot study - Kirschbaum, E. M.; Heyde, K.; Tapper, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The hormonal fluctuations during the phases of the menstrual cycle (MC) have an impact on female athletes` self-reported physical fitness and performance (1) and they also lead to changes in mood and fatigue (2). Female athletes perceive their worst state of fitness and performance during bleeding, the early follicular phase (EFP), while their perceived best state of fitness and performance is in the late follicular phase (LFP) (1). In contrast to that, the physiological ability to recover after exercise is better in the luteal phase (LP) compared to the EFP (3).